Effects of the COVID-19 Pandemic on the Mental Health of Healthcare Providers: A Comparison of a Psychiatric Hospital and a General Hospital - Anzola, Daniel; Limoges, Jacqueline; McLean, Jesse; Kolla, Nathan J. (Frontiers in Psychiatry, 2022)
Background: Before the COVID-19 pandemic, healthcare providers (HCPs) were already experiencing a higher prevalence of mental health disorders compared with non-healthcare professionals. Here, we report on the psychosocial functioning and stress resilience of 240 HCPs who worked during the COVID-19 pandemic in a large-sized psychiatric facility and a large acute care hospital, both located in central Ontario, Canada. Methods: Participants completed five validated psychometric instruments assessing depression, anxiety, and stress (The Depression Anxiety Stress Scales, DASS-21); work-related quality of life (Work-Related Quality of Life Scale, WRQoL); resilience (Connor-Davidson Resilience Scale, CD-RISC); anxiety about the novel coronavirus (Coronavirus Anxiety Scale, CAS); and loneliness (UCLA Loneliness Scale, ULS). Participants from the psychiatric hospital were sampled during the easing of restrictions after the first wave in Ontario, and participants from the acute care hospital were sampled during the height of the second wave. Results: Data showed that HCPs from the acute care hospital reported more anxiety related to COVID-19 compared with the psychiatric hospital staff (p = .002). There were no other significant differences in psychometric scale scores observed between sites or medical disciplines at the acute care hospital. Among all HCPs, being a nurse predicted better quality of life (p = .01) and greater stress resilience (p = .031). Conclusion: These results suggest that HCPs’ anxiety about COVID-19 may vary as a function of the pandemic severity. Compared to other HCPs, nurses may show a unique resiliency to the pandemic. We suggest that emergencies such as the COVID-19 pandemic have a pervasive effect on HCPs. It is important to address HCPs’ mental health needs in terms of crisis management and improve resilience among all HCPs during the inter-crisis period before a new challenge arrives.